Standard of protection of property rights of owners of residential premises in a democratic country – selected problems considered in the light of Polish constitutional law - Pisz, Maciej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The article focuses on presenting key issues revealed in the context of the standard of protection of property rights of owners of residential premises in a contemporary democratic state governed by the rule of law. The considerations presented take into account the perspective of Polish constitutional law and the guarantees of protection of ownership and other property rights as regulated in the Constitution of the Republic of Poland of April 2, 1997 (with particular emphasis on Article 21 and Article 64). The issue addressed in this paper of particular importance from the Polish perspective because, on the one hand, Polish constitutional law formulates relatively broad guarantees for the protection of ownership and other property rights (including those rights of owners of residential premises and tenants – as outlined in Article 21 and Article 64 of the Polish Constitution). On the other hand, there are several practical problems in Poland in this context, including a very significant systemic issue related to the lack of any systemic solutions in the regulation of the short-term rental market by the Polish legislator.